Cinema and Revolution: Russian Constructivism and Dialectical Montage, Foundations of the Political Pedagogy of Eisenstein’s Images - Batista Jr., Natalício (Pontifícia Universidade Católica de São Paulo, 2017)
Russian constructivism and the dialectical montage of images are the foundations of the practice and thought of the vanguard cinema of the Soviet director Sergei Eisenstein. In the context of the struggles and transformations unleashed by the Russian Revolution of 1917, Soviet cinema won international acclaim. Sergei Eisenstein’s filmmaking experiments with the methods of montage and explores socialist and Marxist themes. This article presents the main characteristics of Eisenstein’s work, his contribution to Soviet cinema and the pedagogical and political meaning of the montages in his films The Strike (1924), The Battleship Potemkin (1925) and October (1927).